Content validity of humility scale in Javanese cultural society - Pebriani, Novita; Raharjo, Alim Panggih; Azizah, Siti Nur; Widodo, Prasetyo Budi (University of Merdeka Malang, 2024)
ABSTRACT Humility is an individual who is based on humility so that he can put other people’s perspectives on himself and be able to realize the shortcomings and strengths within the Javanese community. The items developed in this study are in the form of an interval Likert scale consisting of 4 weights, namely strongly agree (SS), agree (S), disagree (TS) and strongly disagree (STS). Validity is carried out on each indicator compiled by researchers with an Aiken’s V limit of 0.8. Here involved experts (expert judgment) with a total of 9 people. The results of the Aikens’ V analysis show that the humility scale in Javanese cultural society developed in this study has good content validity, with a V value of more than 8 in indicator testing, aspects in content validity testing on 54 humility scale items in Javanese society.ABSTRAKHumility adalah individu yang didasari oleh kerendahan hati sehingga dapat menempatkan perspektif orang lain pada dirinya dan mampu menyadari kekurang dan kelebihan didalam diri masyarakat budaya jawa. Aitem yang dikembangkan dalam penelitian ini berupa skala likert interval yang terdiri dari 4 bobot yankni sangat setuju (SS), setuju (S), tidak setuju (TS) dan sangat tidak setuju (STS). Validitas yang dilakukan pada setiap indikator yang disusun peneliti dengan batas Aiken’s V sebesar 0,8. Disini melibatkan ahli (expert judgment) dengan jumlah 9 orang. Hasil dari analisis Aikens’ V menunjukan bahwa skala humility pada masyarakat suku jawa yang dikembangkan pada penelitian ini memiliki validitas isi yang baik, dengan nilai V lebih dari 8 pada pengujian indikator, aspek dalam pengujian validitas isi pada 54 aitem skala humility pada masyarakat budaya jawa